Young Women in South African Call Centres: A Case of Women’s Empowerment or a Repackaging of the Conventional Global Factory? - (:unkn) unknown (My University, 2017)
ICT4D is slowly making inroads into various communities in developing contexts globally, and this slow pace is equally noticeable within the field of gender and development. This paper draws from an ongoing research project that uses a qualitative feminist framework to investigate young women’s participation in the call centre industry in Cape Town, South Africa. The paper further draws on intersectionality to tap into lived experiences of young women working in different call centres to critically explore the “value” for call centres as a project empowering young women economically in the South African context. Drawing from descriptive data collected from young women working as call centre agents, the paper argues that call centres may indeed be a huge ICT4D empowerment project for young women in the South African context, but also cautions that call centres continue to parade the hallmarks of ‘traditional female employment ghettos’.
Keywords: African Research